Person-level changes in oxycodone use after the introduction of a tamper-resistant formulation in Australia - Schaffer, Andrea L. (CMAJ, 2018)
BACKGROUND: Australia introduced tamper-resistant controlled-release (CR) oxycodone in April 2014. We quantified the impact of the reformulation on dispensing, switching and poisonings. METHODS: We performed interrupted time-series analyses using population-representative national dispensing data from 2012 to 2016. We measured dispensing of oxycodone CR (≥ 10 mg), discontinuation of use of strong opioids and switching to other strong opioids after the reformulation compared with a historical control period. Similarly, we compared calls about intentional opioid poisoning using data from a regional poisons information centre. RESULTS: After the reformulation, dispensing decreased for 10–30 mg (total level shift −11.1%, 95% confidence interval [CI], −17.2% to −4.6%) and 40–80 mg oxycodone CR (total level shift −31.5%, 95% CI −37.5% to −24.9%) in participants less than 65 years of age but was unchanged in people 65 years of age or older. Compared with the previous year, discontinuation of use of strong opioids did not increase (adjusted hazard ratio [HR] 0.95, 95% CI 0.91 to 1.00), but switching to oxycodone/naloxone did increase (adjusted HR 1.54, 95% CI 1.32 to 1.79). Switching to morphine varied by age (p < 0.001), and the greatest increase was in participants less than 45 years of age (adjusted HR 4.33, 95% CI 2.13 to 8.80). Participants switching after the reformulation were more likely to be dispensed a tablet strength of 40 mg or more (adjusted odds ratio [OR] 1.40, 95% CI 1.09 to 1.79). Calls for intentional poisoning that involved oxycodone taken orally increased immediately after the reformulation (incidence rate ratio (IRR) 1.31, 95% CI 1.05–1.64), but there was no change for injected oxycodone. INTERPRETATION: The reformulation had a greater impact on opioid access patterns of people less than 65 years of age who were using higher strengths of oxycodone CR. This group has been identified as having an increased risk of problematic opioid use and warrants closer monitoring in clinical practice.